Expression of Neuropeptide F Gene and Its Regulation of Feeding Behavior in the Pea Aphid, Acyrthosiphon pisum - Li, Xiao; Qu, Ming-Jing; Zhang, Yi; Li, Jian-Wen; Liu, Tong-Xian (Frontiers in Physiology, 2018)
Neuropeptide F (NPF) signaling systems are widespread and highly evolutionarily conserved from vertebrates to invertebrates. In fact, NPF has been identified in many insect species and plays regulatory roles in diverse physiological processes, such as feeding, learning, reproduction and stress responses. NPF operates by interacting with the NPF receptor (NPFR). Here, we characterized and determined the presumed role of NPF signaling in the wingless parthenogenetic pea aphid, Acyrthosiphon pisum. Quantitative real-time reverse transcription-PCR (qRT-PCR) revealed that the expression levels of both NPF and NPFR transcripts varied across developmental stages, which implies that the NPF signaling system might participate in the developmental regulation of aphid physiological processes or behaviors. The NPF transcript was mainly detected in the head but not in the gut, whereas the NPFR transcript was mainly detected in both the gut and head. In addition, the NPF transcript levels were markedly up-regulated in starved aphids compared with satiated aphids, and the transcript levels recovered after re-feeding. In contrast, the NPFR transcript levels remained stable in starved and re-fed aphids. Furthermore, RNAi knockdown by the injection of NPF dsRNA into wingless adult aphids significantly reduced their food intake. Further analysis of the modification of aphid feeding behavior on broad bean plants using electrical penetration graphs (EPGs) revealed that both the probing time and the total duration of phloem activity decreased significantly in the NPF treatment group. These results indicated a lower appetite for food after NPF knockdown, which could explain the reduction in aphid food intake. NPF silencing was also shown to reduce reproduction but not survival in aphids. Overall, the results of these experiments suggest that NPF plays an important role in regulation of feeding in A. pisum.